Impact of Giving Patients Your Personal Phone Number in Otolaryngology—Head & Neck Surgery. (April 2023) - Adams, Matthew D.; Wong, Jeff; Gadre, Arun; Greene, Joseph Scott; Milligan, Donna; Paknezhad, Hassan; Purdy, Nicholas; Rager, Jennifer; Wertz, Aileen; Whitenight, Season; Haugen, Thorsen W.
Objective: Patient-provider communication is a major barrier to care, with some providers giving their personal phone number (PPN) to patients for increased accessibility. We investigated participant utilization of provider's PPN, its effect on participant satisfaction, provider's ability to predict abuse of this practice, and evolving provider perceptions. Study Design: Prospective, randomized study. Setting: Single institution, tertiary referral center. Methods: During a 2-week period, otolaryngology patients were randomized to either receive their provider's PPN or not. Providers predicted the likelihood of abuse. All calls/texts were documented for 4 weeks. At the study's conclusion, participants were surveyed using Press Ganey metrics. Providers were surveyed before and after to assess their likelihood of providing patients with their PPN and its impact on work demands. Results: Of the 507 participants enrolled, 266 were randomized to the phone number group (+PN). Of 44 calls/texts from 24 participants, 8 were considered inappropriate. Ten participants were predicted to abuse the PPN, but only one was accurately identified. Participants in the +PN group had a greater mean composite satisfaction score than the control group (4.8 vs 4.3; Welch's t -test, P  < .0011). At the conclusion of the study, providers were more likely to share their PPN (Wilcoxon signed-rank test, P  < .0313), and their perceived impact of this practice on workload was lower (Wilcoxon signed-rank test, P  < .0469). Conclusion: This study demonstrates low patient utilization of provider PPNs, and poor provider predictive ability of patient abuse. Receipt of provider's PPN was associated with improved patient satisfaction.